Peptidoglycan recognition protein (PGRP)-LE and PGRP-LC act synergistically in Drosophila immunity. - Takehana, A.; Yano, T.; Mita, S.; Kotani, A.; Oshima, Y.; Kurata, S. (The EMBO Journal, 2004)
In innate immunity, pattern recognition molecules recognize cell wall components of microorganisms and activate subsequent immune responses, such as the induction of antimicrobial peptides and melanization in Drosophila. The diaminopimelic acid (DAP)-type peptidoglycan potently activates imd-dependent induction of antibacterial peptides. Peptidoglycan recognition protein (PGRP) family members act as pattern recognition molecules. PGRP-LC loss-of-function mutations affect the imd-dependent induction of antibacterial peptides and resistance to Gram-negative bacteria, whereas PGRP-LE binds to the DAP-type peptidoglycan, and a gain-of-function mutation induces constitutive activation of both the imd pathway and melanization. Here, we generated PGRP-LE null mutants and report that PGRP-LE functions synergistically with PGRP-LC in producing resistance to Escherichia coli and Bacillus megaterium infections, which have the DAP-type peptidoglycan. Consistent with this, PGRP-LE acts both upstream and in parallel with PGRP-LC in the imd pathway, and is required for infection-dependent activation of melanization in Drosophila. A role for PGRP-LE in the epithelial induction of antimicrobial peptides is also suggested.